Aydın Uzun1,*, Erhan Akcalı 1 - Aydın Uzun; Erhan Akcalı (International Journal of Secondary Metabolite)
Almond (Prunus amygdalus L.) can grow under dry climate and harsh soil conditions. The fruits are drupe. Seed-propagated almond populations exist in various parts of Turkey. Several studies have been performed to select the promising genotypes among these populations with regard to fruit quality, yield, late foliations and etc. characteristics. Rich almond populations are shown around the foothills of Erciyes Mountain in Kayseri province of Central Anatolia. In this study, some fruit and biochemical characteristics of 34 almond genotypes selected as promising genotypes with regard to late foliation and yield were determined. Significant variations (P < 0.05) were observed in investigated traits of the genotypes. Of selected genotypes, fruit weights varied between 1.5±0.4- 7.6±0.5 g, fruit lengths between 40.7±0.7 - 19.9±2.9 mm, fruit heights between 17.4±0.8 – 10.3±2.1 mm and fruit widths between 27.6±0.7 – 11.8±0.7 mm. With regard to fruit shape of genotypes, 13 were identified as long oval, 12 as elliptical, 5 hearth-shaped and 4 as round. Considering the biochemical characteristics, crude oil contents varied between 54.9 - 42.1% and protein contents varied between 24.6 – 17.7%.